Peran Sistem Informasi Manajemen Dalam Meningkatkan Kinerja Organisasi - Ella, Susy (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
Infoermation is the important element in an organization. Management function which are planning, organizing, actuating, and controlling require a quick, correct, and accurate information. The informationis also needed by the manager in decision making, so that, we need a system for managing the data to be qualified information. The system is called information system. It is built by the organizational functions, where the interaction of collectivity the information system is called Management Information System (MIS). The existence of the MIS will give a positive contribution to improve the organizational performance.